Silage Quality of Sorghum Harvested at Different Times and Its Combination with Mixed Legumes or Concentrate Evaluated in Vitro - . Ardiansyah; K. G. Wiryawan; P.D.M.H. Karti (Media Peternakan, 2016)
The experiment was designed to evaluate the silage quality of sorghum forage varieties of Citayam and BMR 3.6 strain at different harvesting times and the effectiveness of a legumes addition as a concentrate substitute in sorghum forage silage-based diets on in vitro fermentability using rumen fluid of beef cattle. Experimental design for silage quality was completely randomized design with 2 x 3 factorial, i.e., forage sorghum types (Citayam and BMR 3.6) and time of harvesting the forage sorghum (85, 95, and 105 d). Experimental design for in vitro fermentability and digestibility was randomized block design with 2 x 2 factorial arrangement, i.e. types of ration (with 2 levels i.e., a mixture of legumes and concentrate) and types of sorghum forage silages (with 2 levels i.e., Citayam and BMR 3.6). All silages had a good odor, color, and texture. Silage of sorghum harvested at 105 d had better grades and was selected for in vitro studies. The treatment had no effect on pH and organic matter digestibility. BMR 3.6 based silage had greater values of NH3, total VFA, rumen microbial population, methane, and dry matter digestibility. Substitution of concentrate with a mixture of legumes did not affect fermentability, microbe population and digestibility in the rumen. Silage of sorghum strain BMR 3.6 harvested at 105 d had a very good quality and mixing with legumes could replace concentrate in forage sorghum silage based diet on in vitro fermentability and digestibility using beef cattle rumen fluid.